Analisis Pengaruh Goal Orientation dan Work Motivation terhadap Work Role Innovation dengan Self-Leadership sebagai Mediator; Studi pada Perusahaan Media (PT. Surya Citra Televisi) - Masruroh Masruroh; Andana Sasriya (Bina Nusantara University, 2015)
This research has an aim to discover an understand the influence of Goal Orientation and Work Motivation against Work Role Innovation through Self-leadership at PT. Surya Citra Televisi. PT. Surya Citra Televisi engaged in TV broadcasting sector. To see the influence of Goal Orientation and Work Motivation against Work Role Innovation through Self-leadership, this research use a quantitative approach where questionaire used to collect data from a total of 150 employees correspondent and the research method used is path analysis. This analysis is used to determine how much influence of variables Goal Orientation and Work Motivation to Work Role Innovation through Self-leadership at PT. Surya Citra Televisi. The result found in this research is Goal Orientation does influence significantly to Work Role Innovation at PT. Surya Citra Televisi. Work Motivation does influence significantly to Work Role Innovation at PT. Surya Citra Televisi. The indirect influence of Goal Orientation and Work Motivation through Self-leadership against Work Role Innovation is weak while Self-leadership shows strong influence if it acts as an independent variable. Bacause of that, Selfleadership will be more accurate if it acts as an independent variable along with Goal Orientation and Work Motivation.